Recommendations of the International Medical Informatics Association (IMIA) on Education in Biomedical and Health Informatics - Mantas, J.; Ammenwerth, E.; Demiris, G.; Hasman, A.; Haux, R.; Hersh, W.; Hovenga, E.; Lun, K. C.; Marin, H.; Martin-Sanchez, F.; Wright, G. (Methods of Information in Medicine, 2010)
Objective: The International Medical Informatics Association (IMIA) agreed on revising the existing international recommendations in health informatics /medical informatics education. These should help to establish courses, course tracks or even complete programs in this field, to further develop existing educational activities in the various nations and to support international initiatives concerning education in biomedical and health informatics (BMHI), particularly international activities in educating BMHI specialists and the sharing of courseware. Method: An IMIA task force, nominated in 2006, worked on updating the recommendations’ first version. These updates have been broadly discussed and refined by members of IMIA’s National Member Societies, IMIA’s Academic Institutional Members and by members of IMIA’s Working Group on Health and Medical Informatics Education.Results and Conclusions: The IMIA recommendations center on educational needs for health care professionals to acquire knowledge and skills in information processing and information and communication technology. The educational needs are described as a three-dimensional framework. The dimensions are: 1) professionals in health care (e.g. physicians, nurses, BMHI professionals), 2) type of specialization in BMHI (IT users, BMHI specialists), and 3) stage of career progression (bachelor, master, doctorate). Learning outcomes are defined in terms of knowledge and practical skills for health care professionals in their role a) as IT user and b) as BMHI specialist. Recommendations are given for courses /course tracks in BMHI as part of educational programs in medicine, nursing, health care management, dentistry, pharmacy, public health, health record administration, and informatics /computer science as well as for dedicated programs in BMHI (with bachelor, master or doctor degree).To support education in BMHI, IMIA offers to award a certificate for high-quality BMHI education. It supports information exchange on programs and courses in BMHI through its Working Group on Health and Medical Informatics Education.
Keywords: Medical informatics; health informatics; biomedical informatics; education; recommendations; International Medical Informatics Association; IMIA